2022
DOI: 10.1186/s40885-022-00218-1
|View full text |Cite
|
Sign up to set email alerts
|

Home blood pressure monitoring: a position statement from the Korean Society of Hypertension Home Blood Pressure Forum

Abstract: Home blood pressure measurement (HBPM) has the advantage of measuring blood pressure (BP) multiple times over a long period. HBPM effectively diagnoses stress-induced transient BP elevations (i.e., white coat hypertension), insufficient BP control throughout the day (i.e., masked hypertension), and even BP variability. In most cases, HBPM may increase self-awareness of BP, increasing the compliance of treatment. Cumulative evidence has reported better improved predictive values of HBPM in cardiovascular morbid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 90 publications
0
24
0
Order By: Relevance
“… 5 Home BP monitoring can help overcome physician inertia by the provision of multiple readings which allow for better treatment decision-making and informed medication titration thereby improving BP control. 2 , 6 Furthermore, HBPM is an important predictor of target organ damage and provides better prognostic information than office BP and, although the evidence base is still developing, HBPM is suggested by Hypertension Canada to be used in conjunction with standardized office measurement for long-term BP monitoring. 2 , 6 - 12 There exists a paucity of data on uptake, barriers, and facilitators of HBPM in non-dialysis CKD patients, a group likely to benefit from improved BP control due to a high prevalence of hypertension and cardiovascular disease and BP control slowing the trajectory of kidney function decline.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 5 Home BP monitoring can help overcome physician inertia by the provision of multiple readings which allow for better treatment decision-making and informed medication titration thereby improving BP control. 2 , 6 Furthermore, HBPM is an important predictor of target organ damage and provides better prognostic information than office BP and, although the evidence base is still developing, HBPM is suggested by Hypertension Canada to be used in conjunction with standardized office measurement for long-term BP monitoring. 2 , 6 - 12 There exists a paucity of data on uptake, barriers, and facilitators of HBPM in non-dialysis CKD patients, a group likely to benefit from improved BP control due to a high prevalence of hypertension and cardiovascular disease and BP control slowing the trajectory of kidney function decline.…”
Section: Introductionmentioning
confidence: 99%
“…2,6 Furthermore, HBPM is an important predictor of target organ damage and provides better prognostic information than office BP and, although the evidence base is still developing, HBPM is suggested by Hypertension Canada to be used in conjunction with standardized office measurement for long-term BP monitoring. 2,[6][7][8][9][10][11][12] There exists a paucity of data on uptake, barriers, and facilitators of HBPM in nondialysis CKD patients, a group likely to benefit from improved BP control due to a high prevalence of hypertension and cardiovascular disease and BP control slowing the trajectory of kidney function decline. 4,[13][14][15][16] Patient-centered care, which focuses on enabling patients to self-manage aspects of their health care, is encouraged in many CKD management guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…In routine practice at hypertension clinic, the clinic BP is measured by a physician or qualified nurse using a validated oscillometric automated device after resting for 5 min, and the average of at least three measurements taken at 1 min intervals is recorded. Physicians and qualified nurses provided instructions to the participants on how to use a validated oscillometric upper arm cuff device for measuring their home BP [17,18]. To ensure the accuracy of the BP measurement method, patients were requested to bring their HBPM devices to the clinic, where the measurement technique underwent validation by physicians and qualified nurses.…”
Section: Blood Pressure Measurementmentioning
confidence: 99%
“…The median (5th-95th percentiles) number of days on which morning and evening home BP readings were taken by each patient was 13 (6)(7)(8)(9)(10)(11)(12)(13), and the number of morning and evening home SBP readings per patient was 39 (18-39; Table S1).…”
Section: Home Bp Quality Controlmentioning
confidence: 99%
“…3 Current guideline documents and other publications consider out-of-office BP monitoring (ie, home and ambulatory BP) to be an essential component of diagnostic and therapeutic strategies for hypertension. [4][5][6][10][11][12][13][14] The Ohasama study was the first to show that home BP is a more reliable predictor of outcome than office BP, 9 and these findings have been widely replicated and extended. [15][16][17][18][19][20][21][22] Spline regression analysis performed in the HONEST study (Home BP Measurement With Olmesartan Naive Patients to Establish Standard Target BP) found that a morning home SBP of 124 mm Hg was associated with the lowest risk of cardiovascular events.…”
mentioning
confidence: 99%